Gaps in access to oncological treatment in a reference health hospital in the south of Lima in 2019: Brechas de acceso al tratamiento oncológico en un hospital de salud de referencia del Sur de Lima en el año 2019 - Bustamante, Reina I. (2022)
Introduction: Cancer, a chronic disease that has a high incidence with 14.1 million people and more than 8.1 million deaths, generating a large access gap according to the user's perception. Objectives: To determine the gaps in access to cancer treatment in a Hospital in Peru in 2019, due to predisposing, enabling and necessary factors. Method: observational, descriptive, cross-sectional study with 185 patients diagnosed with cancer who were treated at the oncology department of the Hospital María Auxiliadora between March and December 2019, applying a random survey. Results: The predisposing factors for the gap in access to cancer care were: primary education or none (p= 0.000), female gender (p=0.043), being afraid of a cancer diagnosis (p=0.000), being afraid of interventions (p=0.043) and being over 65 years old (p=0.000), having feelings of helplessness (p=0.000). Within the enabling factors as a gap: not having a job (p=0.011), payment for exams in a private way (p=0.035), stop working (p=0.039), payment for medicines in a private way (p= 0.000), resort to the loan (p= 0.009), health expenditure between 501-1000 soles in health (p=0.048). Of the necessary factors: having moderate to severe anemia (p=0.002) or having required more than one treatment in combination (p=0.003). Conclusions: there is a gap for cancer care such as those concerning the predisposing factor (fear of cancer diagnosis and treatment); enabling (infrastructure and equipment, payment for medicines) and necessary factor (severe anemia).